Flavaglines: Their Discovery from Plants Used in Traditional Chinese Medicine, Synthesis, and Drug Development Against Cancer and Immune Disorders - Wang, Dong; Tezeren, Mustafa; Abou-Hamdan, Hussein; Yu, Peng; Nebigil, Canan G.; Désaubry, Laurent (Current Chinese Chemistry, 2022)
Flavaglines, a family of compounds from plants used in traditional Chinese medicine, exhibit a broad range of biological effects, including anticancer, antiviral, cardioprotective, and anti-inflammatory activities. They exert their action by targeting the scaffold proteins called prohibitin-1 and -2 and the mRNA helicases eIF4A and DDX3. Flavaglines are densely functionalized cyclopenta[b]benzofurans that have attracted the attention of some of the most eminent organic chemists. This review provides an overview of the biosynthesis, total synthesis, and pharmacological activities of flavaglines, which have recently culminated with the entrance of a synthetic derivative, Zotatifin, into clinical trials against advanced refractory solid tumors, intolerant to standard treatments.
Keywords: medicinal chemistry